I Wish - King, DeWitt (ACME, 2024)
The letter charts my relationship to geography through a letter to Donald Deskin Jr. From Black geographer junior scholar to pioneering Black geographer, this letter uses Black geographies as an analytic to think through Black geographical knowledge, practice and kinship.